Use of beamforming for detecting an acoustic source inside a cylindrical shell filled with a heavy fluid. (February 2015) - Moriot, J.; Maxit, L.; Guyader, J.L.; Gastaldi, O.; Périsse, J.
Abstract: The acoustic detection of defects or leaks inside a cylindrical shell containing a fluid is of prime importance in the industry, particularly in the nuclear field. This paper examines the beamforming technique which is used to detect and locate the presence of an acoustic monopole inside a cylindrical elastic shell by measuring the external shell vibrations. In order to study the effect of fluid–structure interactions and the distance of the source from the array of sensors, a vibro-acoustic model of the fluid-loaded shell is first considered for numerical experiments. The beamforming technique is then applied to radial velocities of the shell calculated with the model. Different parameters such as the distance between sensors, the radial position of the source, the damping loss factor of the shell, or of the fluid, and modifications of fluid properties can be considered without difficulty. Analysis of these different results highlight how the behaviour of the fluid-loaded shell influences the detection. Finally, a test in a water-filled steel pipe is achieved for confirming experimentally the interest of the presented approach. Highlights: Beamforming is developed for detecting a monopole source from vibration measurements. The vibrational behaviour of a fluid filled shell is analysed. A sensor spacing criterion regarding the vibration field of the shell is defined. Effect of monopole location and damping variations are investigated. The method is tested and validated on a mock-up.